ZEROISASI FONETIK PADA BAHASA KAERA DAN TEIWA - Salimulloh Tegar Sanubarianto (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
Abstract This study aims to identify some of the phonetics change rules of Kaera and Teiwa languages. Therefore, this research uses mix methods. Quantitative methods used to determine the level of differences of Kaera and Teiwa languages. Qualitative methods are used to determine the rules about phonetic changes of both languages. Data collection uses advanced techniques and records with the main instrument 200 Swadesh vocabulary. The data collected were then analyzed using the dialectometry technique to determine the level of differences of Kaera and Teiwa languages, while the Padan Intralingual Crowley technique to determine the rules about phonetic changes of Kaera and Teiwa language. The result of dialectometry analysis shows that the level of differences of Kaera and Teiwa languages ​​is 29—35,5%, meaning the two languages ​​are included in the cognate category. Furthermore, in the vocabulary of Kaera and Teiwa language cognates, zeroization, namely aferesis and apokop are found. Keywords: Kaera, Teiwa, phonetic change